1990
DOI: 10.1136/adc.65.9.953
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cyanotic episodes with severe arterial hypoxaemia and intrapulmonary shunting: a mechanism for sudden death.

Abstract: The pathophysiology of recurrent cyanotic episodes has been investigated in 51 infants and children. Episodes began at a median age of 7 weeks (range 1 day to 22 months, 39 at less than 4 months). They were characterised by the rapidity of onset and progression of severe hypoxaemia with early loss of consciousness from cerebral hypoxia. The most common precipitating factor was a sudden naturally occurring stimulus from pain, fear, or anger. In uncontrolled trials, cyanotic episodes were reduced in frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
4

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 26 publications
1
40
0
4
Order By: Relevance
“…None of these infants (cases or controls) had a structural congenital heart lesion that could have produced a right to left shunt and resultant ventilation/perfusion mismatch. An intermittent intrapulmonary right to left shunt was, therefore, considered to be the most likely cause of these hypoxaemic episodes.5 13 The analysis of breathing patterns during prolonged desaturations performed in the present study confirms our previous observation that the potential to develop a mismatch between ventilation and perfusion may also be present in clinically well preterm infants.…”
Section: Discussionsupporting
confidence: 88%
“…None of these infants (cases or controls) had a structural congenital heart lesion that could have produced a right to left shunt and resultant ventilation/perfusion mismatch. An intermittent intrapulmonary right to left shunt was, therefore, considered to be the most likely cause of these hypoxaemic episodes.5 13 The analysis of breathing patterns during prolonged desaturations performed in the present study confirms our previous observation that the potential to develop a mismatch between ventilation and perfusion may also be present in clinically well preterm infants.…”
Section: Discussionsupporting
confidence: 88%
“…In DiMario's (3) prospective study, as many as four of 95 children had learning disablilities and are in special education classes, although there was no proof that BHS were the cause of these disabilities. One of the patients reported by Southall et al (12) presented with progressive cerebral atrophy shown by computed tomography, although neuropathology was not reported following sudden death.…”
Section: Figure 1) a Rhythm Strip From An Event Recorder At The Time mentioning
confidence: 94%
“…Unexpected death has been reported in children with BHS, although other causes of death were entertained in some cases (10,11). In 1990, Southall et al (12) reported sudden death in eight of 51 infants and young children with recurrent episodes of cyanosis and loss of consciousness precipitated by crying. Autopsies suggested other causes of death in six children, but sudden death could have been precipitated by primary breath-holding in at least two children.…”
Section: Figure 1) a Rhythm Strip From An Event Recorder At The Time mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bilateral ptosis and unilateral miosis, neuroparalytic corneal ulceration and reduced pupillary light reflexes of the right eye indicated oculosympathetic paresis 7,8 , in the absence of spaceoccupying lesion of brain, neck and thorax.…”
Section: Case Historymentioning
confidence: 99%